Differential responses of carbon‐degrading enzyme activities to warming: Implications for soil respiration. (1st August 2018) - Chen, Ji; Luo, Yiqi; García‐Palacios, Pablo; Cao, Junji; Dacal, Marina; Zhou, Xuhui; Li, Jianwei; Xia, Jianyang; Niu, Shuli; Yang, Huiyi; Shelton, Shelby; Guo, Wei; et al.
Abstract: Extracellular enzymes catalyze rate‐limiting steps in soil organic matter decomposition, and their activities (EEAs) play a key role in determining soil respiration (SR). Both EEAs and SR are highly sensitive to temperature, but their responses to climate warming remain poorly understood. Here, we present a meta‐analysis on the response of soil cellulase and ligninase activities and SR to warming, synthesizing data from 56 studies. We found that warming significantly enhanced ligninase activity by 21.4% but had no effect on cellulase activity. Increases in ligninase activity were positively correlated with changes in SR, while no such relationship was found for cellulase. The warming response of ligninase activity was more closely related to the responses of SR than a wide range of environmental and experimental methodological factors. Furthermore, warming effects on ligninase activity increased with experiment duration. These results suggest that soil microorganisms sustain long‐term increases in SR with warming by gradually increasing the degradation of the recalcitrant carbon pool. Abstract : The links between extracellular enzyme activities (EEAs) and soil respiration (SR) under warming scenarios remain poorly understood, despite both EEAs and SR are highly sensitive to temperatures. By synthesizing data from 56 studies, we showed that warming significantly increased ligninase activity by 21.4% and SR by 15.8%, while warming had no effect on cellulase activity. Moreover, increases in ligninase activity were positively correlated with SR and warming duration. These results reveal a novel mechanism that warming‐induced shifts in carbon‐degrading EEAs could contribute to the self‐reinforcing SR to long‐term climate warming.